A retrospective study on rapid plasma reagin testing in patients with Pityriasis rosea. (November 2017) - Halteh, Pierre; Lipner, Shari R
Pityriasis rosea (PR) is an acute self-limited exanthem characterized by oval erythematous patches with scale and may be difficult to differentiate from secondary syphilis. A rapid plasma reagin (RPR) test can be used to rule in secondary syphilis with high sensitivity and specificity. A retrospective study was performed on patients at Weill Cornell Medicine, who were diagnosed with PR from 2000 to 2016 and also received RPR testing at the time of diagnosis. The objective was to assess the frequency of secondary syphilis when the initial clinical impression was PR. Only 2/142 patients (1.4%) had a reactive RPR test. Based on our results, we advocate that careful social and sexual histories be taken in all patients presenting with atypical PR and syphilis screening performed if risk factors are present.